Três ensaios sobre o impacto do capital humano no crescimento econômico regional - Buhse, Ana Paula (2020)
Literature shows the importance of human capital to reduce disparities between regions and, considering this relationship, this thesis comprises three essays emphasizing regional and sectoral economic growth, considering education as a proxy for human capital. In the first essay, human capital is represented by the percentage of the population aged 25 or over with a college degree, while in second and third, the bond percentage in the food industry with higher education is used. In essay 1, the influence of human capital on Brazilian municipalities growth rate is analyzed through the geographic patterns of spatial agglomeration. It was observed that, in southeastern and southern regions, there was significant importance of the High-High clusters between the growth rate and the human capital variable, while the spatial econometric model allows us to conclude that human capital positively influences the rate of Gross Domestic Product (GDP) growth per capita in the cities. The second test verified the food agribusiness geographic patterns arranged in the micro-regions of Brazil in 2016, in order to determine if there is concentration / agribusiness agglomeration around the metropolitan micro-regions. The results show that the food industry favors a more concentrated development, with a high population density of qualified labor, access to consumer market and clustering for productivity gains. Finally, the third essay aimed to analyze the spatial distribution of food industry ties with greater human capital. In this study, it was possible to identify that the presence of human capital is determinant in the participation of ties in the micro-regions that are allocated in all states in the southeastern and southern regions, as well as in some states in the northeast (Ceará and Bahia) and north (Amapá and Roraima). The food industries that are clustered in southeastern and southern micro-regions have links with greater human capital, that is, in the Brazilian regions that are already economically developed and where population are more educated and skilled.